Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Kinerja Pegawai terhadap Kepuasan Kerja - Kasra, Eldy; Ali, Hapzi (Jurnal Ilmu Multidisiplin, 2023)
The effect of leadership style, work environment and employee performance on job satisfaction is a scientific article in the literature study within the scope of the field of science. This article's goal is to develop a hypothesis about the relationship between the factors that will be applied in subsequent studies. Items for research found in academic internet media such as Mendeley, Google Scholar, and online libraries. Open access e-journals and e-books are the source of the research methodology used in Quantitative descriptive analysis. The results of this article: 1) leadership style has an effect on job satisfaction; 2) work environment has an effect on job satisfaction; and 3) employee performance has an effect on job satisfaction.